Negotiating power and tradition: local political elites and the pursuit of sustainable rural development in Gorontalo, Indonesia - Apris Ara Tilome; Andi Asrifan (Department of Government Studies, Universitas Muhammadiyah Makassar, 2025)
Rural development in Indonesia after decentralization is influenced not only by formal state institutions but also by traditional authorities. This study aims to analyze how local political elites in Gorontalo negotiate power and legitimacy through interactions between elected officials and traditional leaders in rural development management. This research uses a qualitative approach with data collection techniques through in-depth interviews, participatory observation, and document analysis in three districts in Gorontalo. The findings show that political elites strategically utilize traditional rituals and kinship networks to consolidate power and garner community support, while traditional leaders maintain their influence by mediating access to state resources. These interactions create hybrid governance that both facilitates and constrains inclusive rural growth. Empirically, this study enriches rural sociology by describing how informal institutions remain embedded in local governance, while theoretically contributing to elite studies by linking symbolic authority to development outcomes. The study concludes that effective rural development policies require not only institutional reform but also critical engagement with cultural mechanisms of legitimacy. In line with the Sustainable Development Goals (SDGs), particularly SDG 1 (No Poverty), SDG 10 (Reduced Inequalities), and SDG 16 (Peace, Justice, and Strong Institutions), the integration of traditional leaders into rural development governance must be accompanied by a framework of accountability to ensure the equitable distribution of resources and the protection of marginalized groups.